Functional implications of orientation maps in primary visual cortex - Erin Koch; Jianzhong Jin; Jose M. Alonso; Qasim Zaidi (Nature Communications, 2016)
Stimulus orientation in the primary visual cortex of primates and carnivores is mapped into a geometrical mosaic but the functional implications of these maps remain debated. Here the authors reveal an association between the structure of cortical orientation maps in cats, and the functions of local cortical circuits in processing patterns and contours.